2002
DOI: 10.1212/wnl.58.7.1115
|View full text |Cite
|
Sign up to set email alerts
|

APOE genotype influences acquisition and recall following traumatic brain injury

Abstract: APOE has been demonstrated to influence traumatic brain injury (TBI) outcome. The relationship between APOE genotype and memory following TBI was examined in 110 participants in the Defense and Veterans' Head Injury Program. Memory performance was worse in those who had an APOE epsilon 4 allele (n = 30) than those who did not (n = 80), whereas genotype groups did not differ on demographic or injury variables or on measures of executive functioning. These data support a specific role for the APOE protein in mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(147 citation statements)
references
References 10 publications
3
140
1
3
Order By: Relevance
“…Furthermore, APOE4ϩ individuals were twice as likely as APOE4Ϫ individuals to be dead, comatose, or severely disabled 6 months after TBI (Teasdale et al, 1997). In addition to the poor general clinical outcome associated with APOE4, memory performance within 6 months of head injury was worse in APOE4ϩ patients compared with APOE4Ϫ patients (Crawford et al, 2002), whereas APOE4 led to worse motor function after TBI (Lichtman et al, 2000). Mild, repetitive head injury also appears to interact with APOE.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, APOE4ϩ individuals were twice as likely as APOE4Ϫ individuals to be dead, comatose, or severely disabled 6 months after TBI (Teasdale et al, 1997). In addition to the poor general clinical outcome associated with APOE4, memory performance within 6 months of head injury was worse in APOE4ϩ patients compared with APOE4Ϫ patients (Crawford et al, 2002), whereas APOE4 led to worse motor function after TBI (Lichtman et al, 2000). Mild, repetitive head injury also appears to interact with APOE.…”
Section: Discussionmentioning
confidence: 97%
“…Previous work from the veteran population have shown that APOE‐ ε 4(+) patients experienced more difficulty with memory compared to those who were APOE‐ ε 4(−) following equally severe TBI, as measured on the CVLT‐II verbal memory and fluency measures at 6 months (Crawford et al., 2002). Similarly, Anderson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Han and colleagues reported improved neuropsychological outcome at 1 month was associated with APOE‐ ε 4 in the military population (Han et al., 2007), whereas Crawford et al. (2002) reported memory and verbal impairment in military personnel with APOE‐ ε 4 within 6 months of injury. Using an extensive neuropsychological battery at 3 and 6 weeks postinjury, Liberman et al.…”
Section: Introductionmentioning
confidence: 99%
“…In some, 40-80% of patients with AD possess at least one apoE4 allele (12). Likewise, apoE4 is associated with earlier onset, progression, or severity of head trauma (13)(14)(15)(16)(17)(18)(19), stroke (20,21), complications after coronary artery bypass surgery (22,23), Parkinson's disease (24)(25)(26)(27), amyotrophic lateral sclerosis (28)(29)(30)(31)(32), multiple sclerosis (33,34), diabetic neuropathy (35), sleep apnea (36), Lewy body disorders (37), and CNS ischemia (38).…”
Section: Apoe and Neuropathologymentioning
confidence: 99%